Analysis of the Hybrid of Mudar/Snake Grass Fiber-Reinforced Epoxy with Nano-Silica Filler Composite for Structural Application. (5th January 2022) - Jenish, I.; Sahayaraj, A. Felix; Suresh, V.; Mani raj, J.; Appadurai, M.; Irudaya Raj, E. Fantin; Nasif, Omaima; Alfarraj, Saleh; Kumaravel, Ashok Kumar
Abstract : Natural fiber composite materials are competent materials that may replace conventional synthetic materials where the strength to weight ratio is essential. In this paper, the mechanical characteristics of composites made up of randomly oriented natural fibers (mudar fiber and snake grass fiber) with nano-silica filler are detailed for the first time. From the various literature surveys, the critical length of mudar and snake grass fiber is chosen as 40 mm and 30 mm, respectively. The test samples were prepared with a fiber content of 10%, 20%, 30%, and 40% with an equal amount of mudar and snake grass fiber. The percentage of nano-filler is maintained as constant as 3% with all the compositions. The composites showed that the highest mechanical properties were found at 30% fiber volume. The maximum tensile strength is 45 MPa, and the flexural strength is 51 MPa. The maximum impact strength is 4.5 J. Sample ID 3 provided the best results compared to other proportions. The fiber/matrix adhesion was investigated using a scanning electron microscope (SEM). These predominant mechanical properties make it easier for the implementation of the prepared composite material in structural and automotive applications.